Revisiting the Electrochemical Lithiation Mechanism of Aluminum and the Role of Li‐rich Phases (Li1+xAl) on Capacity Fading. Issue 12 (30th April 2019) - Qin, Bingsheng; Diemant, Thomas; Zhang, Huang; Hoefling, Alexander; Behm, R. Jürgen; Tübke, Jens; Varzi, Alberto; Passerini, Stefano
Abstract: Aluminum is an appealing anode material for high‐energy‐density lithium‐ion batteries (LIBs), owing to its low cost, environmental benignity, high specific capacity, and lower relative volume expansion compared with other alloying materials. However, both, the working and capacity fading processes are not yet consistently and comprehensively understood, which has largely hindered its development. In this study, the electrochemical alloying process of aluminum anodes with lithium is systematically studied by the combination of several in situ and ex situ techniques, providing new insights into phase transitions, electrode dynamics, and surface chemistry. Particular attention is paid to the role of the Li‐rich alloys (Li1+ x Al). Its existence on the surface of the Al electrode is unexpectedly observed, and its growth in the electrode bulk is found to be strictly correlated with cell failure. Interestingly, cell failure can be delayed by choosing an appropriate electrolyte. This work contributes to a solid and comprehensive understanding of the puzzling Al (de‐)lithiation processes, which is fundamental and highly enlightening for future research work on Al and other alloyed anodes. Abstract : The case of missing Li : Systematic investigation of the electrochemical (de‐)lithiation process of the Al anode reveals an incomplete process with multiple alloying/dealloying steps. The existence of Li‐rich alloy phases is unexpectedly observed on the Al electrode surface. In addition, its growth in the electrode bulk is found to be strictly correlated with cell failure, which, interestingly, can be delayed by choosing an appropriate electrolyte.